Tunable Endo/Exo Selectivity in Direct Catalytic Asymmetric 1,3‐Dipolar Cycloadditions with Polyfunctional Lewis Acid / Azolium–Aryloxide Catalysts - Bürstner, Adrian; Becker, Patrick M.; Allgaier, Alexander; Pfitzer, Lucca; Wanner, Daniel M.; Dollinger, Johanna; Willig, Felix; Herrmann, Justin; Miskov‐Pajic, Vukoslava; Hans, Andreas C.; Frey, Wolfgang; Slageren, Joris; et al. (Angewandte Chemie International Edition, 2025)
Catalytic asymmetric 1,3‐dipolar cycloadditions (1,3‐DCA) using iminoesters as ylide precursors offer a powerful approach to accessing stereochemically complex, biologically relevant pyrrolidines. Although previous studies have already achieved impressive stereoselectivities, catalytic productivity remains a challenge, with turnover numbers (TON) typically below 20. In this article, we introduce a novel concept for catalytic 1,3‐DCA that enables remarkable productivity for both endo (TON up to 4000) and the more challenging exo products (TON up to 1500). This approach, making use of modular polyfunctional Lewis acid/azolium‐aryloxide catalysts, allows for precise control over endo‐ and exo‐diastereoselectivity. The switch from endo‐ to exo‐selectivity is accomplished by modifying the metal center, the azolium moiety, and steric factors. As detailed DFT studies reveal, both the endo‐ and exo‐selective catalyst systems exhibit an almost perfect spatial alignment of their key functional sites, allowing for a unique interplay of Brønsted acids and bases, Lewis acids, and hydrogen bonding. The computational studies further demonstrate that these polyfunctional catalysts dramatically lower the energetic barriers of the concerted or stepwise cycloaddition key steps. However, they also precisely orchestrate and accelerate all accompanying transformations—reminiscent of enzymatic machineries. A novel concept for catalytic asymmetric 1,3‐dipolar cycloadditions with iminoesters employs modular polyfunctional Lewis acid/azolium‐aryloxide betaine catalysts, controlling endo‐ and exo‐selectivity through adjustments of metal center, azolium, and sterics. DFT studies reveal an almost perfect spatial fit of functional sites, enabling precise orchestration of the catalytically relevant moieties involved—reminiscent of enzymatic catalysis.